Dampak Cashless dan Cardless Society Bagi Kaum Milenial - Hermaya Ompusunggu; Poniman Poniman (Prosiding, 2023)
This study aims to analyze the impact of a cashless and cardless society on millennials. This research is a qualitative social research using primary data. Problem identification is supported by the VostViewer tool. Data collection techniques include interviews, observation and reviewing cashless and cardless practices. Meanwhile, the data analysis technique used in this research is presenting data and drawing conclusions by looking at social realities related to the development of a cashless and cardless society. The results of this research are that there are many pros and cons to the cashless and cardless phenomenon, because some believe that this phenomenon brings more benefits, while others think otherwise. Apart from that, several reasons why millennials use cashless and cardless are to control expenses, avoid crime, make it easier to use E-Wallet and are incredibly practical. This indicates that the acceptance of a digital-based payment application can be analyzed through positive responses from the public, especially millennials.